Report of the UNESCO Educational Planning Mission to Trinidad and Tobago 15th March, 1964 - 5th June 1964 - UNESCO. Education Planning Mission (UNESCO, 1964)
The UNESCO Mission to Trinidad and Tobago in 1964 attempted to: 1) appraise the existing educational effort, with particular emphasis on those features that enhance or detracted from its capacity, efficiency, or potentiality to achieve the declared aims and targets; 2) Impress on all the significance of the incorporation and integration into the Ministry of Education of a small planning unit; 3) Stress the need to effectively link this planning unit with the central planning machinery; and 4) Identify projects that would serve to accelerate the pace of educational, social, and economic development. The report records the team’s efforts at: a) arriving at some conclusions as to how educational programmes had been planned and the efforts coordinated; b) making a close study of the educational system in operation in order to gain a fuller and more practical realization of the problems that beset the administration, teachers, students and parents; c) determining the future needs of the country in terms of skills and translating these into the future demands for levels and types of education; and d) demonstrating the planning process in a practical manner.
Keywords: Mission reports